1983
DOI: 10.1111/j.1423-0410.1983.tb01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Associated IgM Levels in Thrombocytopenia1

Abstract: Platelet-associated IgG (PAIgG) and IgM (PAIgM) levels were quantitated in patients with thrombocytopenias of various etiologies. 32 of 34 patients with immune thrombocytopenia had elevated PAIgG, 8 of the 34 patients had elevated PAIgM levels. Only 1 patient suffering from immune thrombocytopenia had elevated PAIgM with normal PAIgG levels. Elevated PAIgM was most often associated with elevated PAIgG except for the following: 2 patients with lymphoproliferative disorders, 1 patient with heparin-induced thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Varticovski et al [15] revealed antiplatelet activity of monoclonal IgM in a WM case. Two groups reported patients with WM-associated immune thrombocytopenia who showed elevated PA-IgM levels in contrast to normal PA-IgG levels [13,16]. In contrast, our case developed thrombocytopenia with increased PA-IgG in the course of WM.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Varticovski et al [15] revealed antiplatelet activity of monoclonal IgM in a WM case. Two groups reported patients with WM-associated immune thrombocytopenia who showed elevated PA-IgM levels in contrast to normal PA-IgG levels [13,16]. In contrast, our case developed thrombocytopenia with increased PA-IgG in the course of WM.…”
Section: Discussioncontrasting
confidence: 81%
“…A few reports have referred to the mechanism of immune thrombocytopenia associated with WM, and both platelet-associated IgM (PA-IgM) and IgG (PA-IgG) have been shown to be a possible etiology [13,[15][16][17][18]. In this report, we show a case of immune thrombocytopenia in WM with IgM and IgG paraproteins, which improved after chemotherapy against WM.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation